2017
DOI: 10.1159/000481261
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Proteasome Pathway by Nano-Curcumin and Curcumin in Retinal Pigment Epithelial Cells

Abstract: Introduction: Curcumin has multiple biological effects including the modulation of protein homeostasis by the ubiquitin-proteasome system. The purpose of this study was to assess the in vitro cytotoxic and oxidative effects of nano-curcumin and standard curcumin and characterize their effects on proteasome regulation in retinal pigment epithelial (RPE) cells. Methods: Viability, cell cycle progression, and reactive oxygen species (ROS) production were determined after treatment with nano-curcumin or curcumin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…This study concluded that patients who received CFZ and with low potential for proteasome activity recovery may suffer from both acute and long-term endothelial dysfunction (48). Endothelial cell homeostasis depends on the ubiquitinproteasome system, which induces oxidative stress in the cells and regulates the expression of endothelial nitric oxide synthase (49). The proteasome inhibitor CFZ causes the plasma of cancer cells, cardiomyocytes, and endothelial cells to accumulate with unfolded, dysfunctional proteins, which may lead to impaired vasodilation, excessive oxidative stress, inflammation, cell apoptosis, and autophagy (50,51).…”
Section: Discussionmentioning
confidence: 90%
“…This study concluded that patients who received CFZ and with low potential for proteasome activity recovery may suffer from both acute and long-term endothelial dysfunction (48). Endothelial cell homeostasis depends on the ubiquitinproteasome system, which induces oxidative stress in the cells and regulates the expression of endothelial nitric oxide synthase (49). The proteasome inhibitor CFZ causes the plasma of cancer cells, cardiomyocytes, and endothelial cells to accumulate with unfolded, dysfunctional proteins, which may lead to impaired vasodilation, excessive oxidative stress, inflammation, cell apoptosis, and autophagy (50,51).…”
Section: Discussionmentioning
confidence: 90%
“…It has significant effects on cell migration, tumor development, and angiogenesis. Epoxomicin may lead to an imbalance between MMP-2 and TIMP-1 in ARPE-19 cells, resulting in the occurrence of retinal fibrosis (37). Since in most cases, transcription factors (TFs) are always the key regulators of gene expression and cellular functions, and their dysregulation has been implicated in various pathological conditions including neovascular diseases (38,39), we focused on the only TF among the top 10 pivotal DEGs, SPI1, for further study.…”
Section: Discussionmentioning
confidence: 99%